Analysis of Land Subsidence in Peatlands in the Awareness Area of Pekanbaru, Riau, Indonesia - Husnul Kausarian; Windi Indra Sari; Fitri Mairizki; Batara Batara; Adi Suryadi (Politeknik Negeri Batam, 2023)
This study area is administratively located in Parit Indah District, Bukit Raya District, Pekanbaru City, Riau Province. Geographically, the research area is located at coordinates 0° 28' 30.92